(untitled) (Jurnal Ipteks Terapan, 2023)
This research aims to find out what strategies are carried out by Padang City MSMEs to improve their business performance by developing superior human resource competencies. The problem is focused on limited human resources, the existence of these human resources limitations can then directly limit the movement of Indonesian micro and small businesses so that they can compete sectorally in the domestic market or in the global market. The research method used is descriptive qualitative research using purposive sampling research techniques for selecting informants. Data collection was carried out by means of observation, interviews and documentation studies. It can be seen that the results of this research show that the problems that occur in the MSME sector are quite complex due to the multidimensional side effects of the pandemic on the businesses of MSME players, therefore a sophisticated strategy is needed so that the MSME ecosystem can continue to develop sustainably in Padang City. The population and sample used in this research were 100 respondents. This study concludes that Knowledge and Skills and Information Technology have a significant effect on MSME Performance. Meanwhile, capability does not have a significant effect on the performance of Padang City MSMEs. And Information Technology mediates the knowledge and ability variables on the performance of Padang City MSMEs